HAK ASASI MANUSIA DAN PERLINDUNGAN HUKUM TERHADAP KEKERASAN ANAK DALAM KEHIDUPAN RUMAH TANGGA - Kurniawati, Sindy Mareta (Universitas Nurul Jadid, 2024)
Domestic violence against children is a serious human rights violation that significantly impacts their physical, mental, and social development. Homes, which should serve as a safe haven for children, often become places where their rights are violated. This research examines the causes of domestic violence against children, including economic, psychological, social, and cultural factors. It also elaborates on the resulting impacts, such as psychological disorders, low self-esteem, and disruptions in social development. The legal framework in Indonesia, including the 1945 Constitution, the Child Protection Act, and the Domestic Violence Eradication Act, provides a strong foundation for protecting children from violence. However, law enforcement is often hindered by a lack of public awareness, social stigma, and weaknesses in the justice system. This study highlights the importance of a holistic approach that encompasses community education, police training, expanded rehabilitation services, and cross-sector collaboration to create a safe and supportive environment for children's development.